2018
DOI: 10.1186/s12931-018-0909-6
|View full text |Cite
|
Sign up to set email alerts
|

The utility of biomarkers in diagnosis of aspirin exacerbated respiratory disease

Abstract: BackgroundAspirin-exacerbated respiratory disease (AERD) is a distinct eosinophilic phenotype of severe asthma with accompanying chronic rhinosinusitis, nasal polyposis, and hypersensitivity to aspirin. Urinary 3-bromotyrosine (uBrTyr) is a noninvasive marker of eosinophil-catalyzed protein oxidation. The lack of in vitro diagnostic test makes the diagnosis of AERD difficult. We aimed to determine uBrTyr levels in patients with AERD (n = 240) and aspirin-tolerant asthma (ATA) (n = 226) and to assess whether it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…[81][82][83] Peripheral blood eosinophilia is commonly observed in patients with N-ERD. 84 During aspirin provocation, the number of blood eosinophils decreases, 85 and activated eosinophils accumulate in the respiratory tract, 86 although the biomarkers of eosinophil activation such as 3-bromotyrosine and eosinophil-derived neurotoxin in urine do not increase. 87 Another unique inflammatory condition in N-ERD is the presence of eosinophils or other granulocytes in peripheral blood and airway tissues adhered to platelets, 88,89 which provide LTA4 to granulocytes and participate in CysLT overproduction.…”
Section: Nsaid-exacerbated Respiratory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…[81][82][83] Peripheral blood eosinophilia is commonly observed in patients with N-ERD. 84 During aspirin provocation, the number of blood eosinophils decreases, 85 and activated eosinophils accumulate in the respiratory tract, 86 although the biomarkers of eosinophil activation such as 3-bromotyrosine and eosinophil-derived neurotoxin in urine do not increase. 87 Another unique inflammatory condition in N-ERD is the presence of eosinophils or other granulocytes in peripheral blood and airway tissues adhered to platelets, 88,89 which provide LTA4 to granulocytes and participate in CysLT overproduction.…”
Section: Nsaid-exacerbated Respiratory Diseasementioning
confidence: 99%
“…Peripheral blood eosinophilia is commonly observed in patients with N‐ERD 84 . During aspirin provocation, the number of blood eosinophils decreases, 85 and activated eosinophils accumulate in the respiratory tract, 86 although the biomarkers of eosinophil activation such as 3‐bromotyrosine and eosinophil‐derived neurotoxin in urine do not increase 87 .…”
Section: Clinical Characteristics and Pathophysiology Of Adult‐onset mentioning
confidence: 99%
“…However, these data are still controversial. 22 23 24 There have also been preliminary studies showing that uLTE4 levels might be increased in NECD. 25 26 Whether the measurement of basal uLTE4 levels could be a diagnostic marker for any phenotype of NSAID hypersensitivity is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…This is a stable end product which can accumulate in plasma and urine. Urinary LTE4 has been demonstrated to be a reliable biomarker of several inflammatory disease conditions including AERD 11‐14 . Previous data have shown that a urine LTE4 (uLTE4) liquid chromatography–mass spectrometry (LC–MS) assay cutoff of 166 pg/mg Cr suggested the presence of aspirin sensitivity with 89% specificity among patients with a clinical history of aspirin sensitivity 12 …”
Section: Introductionmentioning
confidence: 99%